Pharmacokinetics and pharmacodynamics of ximelagatran, a novel oral direct thrombin inhibitor, in young healthy male subjects - Eriksson, Ulf G.; Bredberg, Ulf; Gislén, Kristina; Johansson, Linda C.; Frison, Lars; Ahnoff, Martin; Gustafsson, David (European journal of clinical pharmacology, 2003)
Ximelagatran is a novel, oral direct thrombin inhibitor designed to overcome the low and variable oral absorption of melagatran, its active form. The pharmacokinetics and pharmacodynamics of ximelagatran following single and repeated oral administration were investigated. The primary objectives were to determine the dose linearity and reproducibility of melagatran exposure and the influence of food intake. Two open-label studies were performed in healthy male subjects. Study I was a dose-escalation study, in which subjects received single oral doses of ximelagatran (1-98 mg). Study II was a randomised, two-way crossover study consisting of two 5-day treatment periods, in which subjects received a 20-mg oral dose of ximelagatran twice daily, either before breakfast and with dinner, or with breakfast and after dinner. Ximelagatran was rapidly absorbed and converted to melagatran, which was the predominant compound in plasma. The mean (+/- standard deviation) bioavailability of melagatran was 22.2+/-4.3% and 17.4+/-2.8% after single and repeated dosings, respectively. The maximum plasma concentration of melagatran and the area under the melagatran plasma concentration-time curve (AUC) increased linearly with dose. Inter- and intra-subject variability in melagatran AUC was 8% and 12%, respectively, with no relevant food- or time dependence. Anticoagulation, assessed as activated partial thromboplastin time, was correlated with melagatran plasma concentration. There was virtually no increase in capillary bleeding time over the dose range studied, and ximelagatran was well tolerated. After oral administration of ximelagatran to healthy male subjects, the pharmacokinetic and pharmacodynamic profile of melagatran is predictable and reproducible.